A simplified multi-criteria evaluation model for landfill site ranking and selection based on AHP and GIS - Khan, Debishree; Samadder, Sukha Ranjan (Journal of Environmental Engineering and Landscape Management, 2015)
This study used GIS based Multi-criteria Decision Analysis (MCDA) approach for evaluating the most environmentally suitable landfill sites in the study area. The weights of relative importance of the factors guiding landfill siting were estimated using pair-wise comparisons in AHP. The maps showing suitable landfill sites were generated applying a weighted linear combination (WLC) in GIS using a comparison matrix to aggregate different significant scenarios associated with environmental and economic objectives. To determine the appropriate areas where landfill sites can be located, thematic maps for all the criteria were generated using GIS. A final map was produced showing suitability for the location of the landfill sites. The suitable sites having an area equal to or above 4 ha at one place and 90% of which is barren land were considered suitable for landfill. The selected candidate sites were ranked to get the most desirable sites for landfill.